A randomised controlled trial of memory flexibility training (MemFlex) to enhance memory flexibility and reduce depressive symptomatology in individuals with major depressive disorder. (November 2018) - Hitchcock, Caitlin; Gormley, Siobhan; Rees, Catrin; Rodrigues, Evangeline; Gillard, Julia; Panesar, Inderpal; Wright, Isobel M.; Hammond, Emily; Watson, Peter; Werner-Seidler, Aliza; Dalgleish, Tim
Abstract: Successful navigation within the autobiographical memory store is integral to daily cognition. Impairment in the flexibility of memory retrieval can thereby have a detrimental impact on mental health. This randomised controlled phase II exploratory trial ( N  = 60) evaluated the potential of a novel intervention drawn from basic science – an autobiographical Memory Flexibility (MemFlex) training programme – which sought to ameliorate memory difficulties and improve symptoms of Major Depressive Disorder. MemFlex was compared to Psychoeducation (an evidence-based low-intensity intervention) to determine the likely range of effects on a primary cognitive target of memory flexibility at post-intervention, and co-primary clinical targets of self-reported depressive symptoms and diagnostic status at three-month follow-up. These effect sizes could subsequently be used to estimate sample size for a fully-powered trial. Results demonstrated small-moderate, though as expected statistically non-significant, effect sizes in favour of MemFlex for memory flexibility ( d  = 0.34, p  = .20), and loss of diagnosis (OR = 0.65, p  = .48), along with the secondary outcome of depression-free days ( d  = 0.36, p  = .18). A smaller effect size was observed for between-group difference in self-reported depressive symptoms ( d  = 0.24, p  = .35). Effect sizes in favour of MemFlex in this early-stage trial suggest that fully-powered evaluation of MemFlex may be warranted as an avenue to improving low-intensity treatment of depression. Trial registration: ClinicalTrials.gov, IdentifierNCT02371291 . Highlights: Trial evaluates a mechanism-driven autobiographical memory-based intervention. Key aim was to prepare for a larger trial of MemFlex. Superior treatment effect sizes for MemFlex compared to Psychoeducation. A larger trial is now indicated to determine the treatment efficacy of MemFlex.